2017
DOI: 10.1111/jvim.14883
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Evaluation of Liver Hemodynamic Indices in Overweight and Obese Dogs

Abstract: BackgroundHepatic circulatory disturbances have been associated with obesity and fatty liver in humans. In the veterinary literature, however, there is limited information regarding the effects of different body condition scores (BCS) on liver hemodynamic indices in dogs.ObjectivesTo investigate the influence of BCS on liver hemodynamic indices.AnimalsFifty‐three client‐owned dogs of various breeds were included.MethodsProspective observational study. Dogs were divided into 3 BCS groups using a 5‐point scale: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Contrary to the hypothesis, obesity and congestion index were not positively associated. In a recent study, 8 obese dogs were shown to have lower mean portal velocity and PBFV as compared to dogs of ideal body condition. In obese humans, hepatocytes enlarge because of lipid droplets, which results in compression of hepatic vessels and hence increased vascular resistance and decreased compliance 12 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Contrary to the hypothesis, obesity and congestion index were not positively associated. In a recent study, 8 obese dogs were shown to have lower mean portal velocity and PBFV as compared to dogs of ideal body condition. In obese humans, hepatocytes enlarge because of lipid droplets, which results in compression of hepatic vessels and hence increased vascular resistance and decreased compliance 12 .…”
Section: Discussionmentioning
confidence: 93%
“…Each gallbladder wall and vessel cross‐sectional area were measured twice by a single observer (a radiology resident under supervision of a board‐certified veterinary radiologist) and the measurements averaged. Congestion index and PBFV were calculated as previously described 8 . Additionally, the medical record was used to collect the following variables: final diagnosis, breed, sex, neuter status, age, weight, body condition score (BCS), sedation duration, other drugs used, and heart rate during sedation.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, most of the animals were mixed breed. The authors have attributed it of some country bias, since it is one of the most common breeds in Brazil [5,8,14,24,30,48].…”
Section: Discussionmentioning
confidence: 99%
“…The selection criteria for inclusion of the animals were based on the complete history, compatible clinical signs to the disease, laboratory exams such as CBC (PocH-100iv Diff, Sysmex) 2 , urinalysis, and biochemical profile (Cobas Mira Plus, Roche) 3 , Systolic Blood Pressure (SBP) was monitored by non-invasive Doppler (Doppler Ultrasound device) 4 , and abdominal ultrasonographic evaluation (Mylab AlphaVET, Esaote) 5 . Dogs diagnosed with concurrent AKI, sepsis, pancreatitis, coagulation disorder, infectious disease, and nephrolithiasis or had a previous history of familial or congenital renal disease, congestive heart failure, autoimmune disease, and neoplasia were automatically excluded from the study.…”
Section: Selection Criteriamentioning
confidence: 99%
“…In veterinary medicine, spectral Doppler examinations of hepatic veins have been carried out. These investigations were used for the analysis of different hemodynamic conditions in healthy anesthetized dogs, to estimate central venous pressure, in patients with different degrees of tricuspid insufficiency, as well in overweight and obese dogs . However, this technique has not been widely used for assessment of the RV.…”
Section: Introductionmentioning
confidence: 99%